Observations of Lower Tropospheric Water Vapor Structures in GOES‐16 ABI Imagery. Issue 24 (18th December 2018) - Grasso, Lewis; Bikos, Dan; Miller, Steven
Abstract: During the afternoon of 16 April 2017 over Durango, Mexico, Geostationary Operational Environmental Satellite (GOES)‐16 Advanced Baseline Imager (ABI) imagery near 1.38 and 7.34 μm exhibited nonstationary banded features. Alternating patterns of bright (dry) and dark (moist) bands were evident in images of 1.38‐μm reflectance, while corresponding warm (dry) and cool (moist) bands were evident in images of 7.34‐μm brightness temperatures. Based on observations, ambient southwesterly flow across the region is hypothesized to have channeled water vapor through major valleys over western Durango, followed by terrain lifting of water vapor over the plateau of central Durango. Due to lifting, moist bands appeared relatively cool in imagery near 7.34 μm. Similar bright and dark banded patterns were also evident in ABI imagery over Chihuahua, Mexico, on 8 May 2017. During the afternoon over Chihuahua, broken linear segments of cumulus formed within moist portions of the bands. Imagery from the 12.3‐ to 10.3‐μm split window difference also supported the presence of moist bands. In the 8 May 2017 case, the banded features are hypothesized to be the result of horizontal convective rolls. Observations suggested that dark (moist) bands in imagery near 1.38 μm corresponded to the rising branch of horizontal rolls. Due to vertical motion, broken linear segments of cloud streets formed within the rolls. One consequence of newly identified features of the clear‐sky water vapor field indicated the importance of new ABI measurements to aid forecasters in their interpretation of complex mesoscale dynamics. Plain Language Summary: Satellite imagery near 1.38 μm has the primary purpose of detecting cirrus clouds during the daytime. However, when skies are clear, water vapor contents are low, and terrain heights are high; imagery near 1.38 μm may capture detailed atmospheric motion within the first thousand feet above the ground. Two cases are presented in this manuscript: The first occurred on 16 April 2017, and the second occurred on 8 May 2017. Both cases occurred over elevated portions of northern Mexico: Durango and Chihuahua. Cirrus clouds are detected near 1.38 μm because of the interaction of energy from the Sun and water vapor in the air. If water vapor amounts are large, then the cirrus clouds appear bright while the ground appears black. However, if water vapor amounts are low, then the motion of water vapor near the ground can be captured. Key Points: Geostationary imagery of the 1.38‐micrometer cirrus band during the daytime is useful in detecting features other than upper tropospheric cirrus Unlike polar‐orbiting platforms, imagery from geostationary platforms provides superior temporal sampling that facilitates animation and interpretation of imagery of the cirrus band Flows associated with boundary layer features are captured within elevated and complex terrain